PENGARUH KUALITAS PELAYANAN, PENANGANAN KOMPLAIN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL MEDIASI - Ruth Andita Hayu Tejaningtyas (Riset Manajemen dan Akuntansi, 2015)
Customer loyalty will be formed if the consumer was satisfied with the company's service. This shows that customer satisfaction directly affects customer loyalty and customer satisfaction as well as a mediating variable affecting service quality on customer loyalty. This study aimed to analyze the effect of quality of service, complaint handling, image customer loyalty with customer satisfaction as a mediating variable. The population in this study were all clients of PT. AIA Financial Branch of Surakarta. Sampling technique in this study using a purposive sampling. Methods for collecting data using questionnaires and data analysis methods using Structural Equation Modeling. Based on the analysis and discussion, it can be concluded service quality and significant positive effect on customer satisfaction. Handling complaints has significant positive effect on customer satisfaction. Corporate image has significant positive effect on customer satisfaction. Service quality has positive but not significant effect on customer loyalty. Handling complaints is positive but not significant effect on customer loyalty. Corporate image is positive but not significant effect on customer loyalty. Customer satisfaction has significant positive effect on customer loyalty. Customer satisfaction does not mediate the effect of service quality, complaints handling and corporate image on customer loyalty. Keywords: quality of service, complaint handling, image, customer loyalty, customer satisfaction.